A bifunctional mitochondrial targeting AIE-active fluorescent probe with high sensitivity to hydrogen peroxide and viscosity for fatty liver diagnosis. (22nd June 2021) - Xu, Hong; Zhong, Jiehong; Zhuang, Weihua; Jiang, Jizhou; Ma, Boxuan; He, Haiyang; Li, Gaocan; Liao, Yanbiao; Wang, Yunbing
Abstract : A mitochondrial targeting AIE-active fluorescent probe with highly sensitive dual-detection of hydrogen peroxide and viscosity for fatty liver diagnosis. Abstract : AIE fluorophores have been developed as bioimaging probes due to their strong brightness at high concentration and increase of the photostability to promote highly recognizable cellular signaling. However, conventional AIE fluorescent probes for bioimaging just solely lighten the cells or tissues, suffering from the limitation of satisfying the requirement of disease diagnosis. Herein, we report an AIE-active bioprobe (TPP-Tba ) for linear fluorescence response and qualitative detection of hydrogen peroxide (H2 O2 ) and viscosity with a wide detection range and a low detection limit. TPP-Tba displays an impressive ability of distinguishing normal cells and pathological cells. Furthermore, fatty liver tissue can also be efficiently distinguished from normal liver tissue, attributed to the great H2 O2 and viscosity dual-response as well as the specific targeting to mitochondria by TPP-Tba . Given the high sensitivity for H2 O2 and viscosity, great biocompatibility, high specificity to mitochondria, and impressive ability of distinguishing normal tissue and pathological tissue, we envisage that this novel TPP-Tba probe would open a new window for designing novel bioprobes for disease diagnosis.